2016
DOI: 10.1111/jfq.12243
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Bacterial Contamination Sources in Meat Production Line

Abstract: Bacterial contamination during slaughtering process is a safety problem and concern for shelf life in meat production. We compare two different slaughter lines, sheep and cattle samples from Iranian slaughterhouse using PCR‐denaturing gradient gel electrophoresis (DGGE) analysis for evaluation the sources of bacterial contaminations. Bacterial diversity was significantly different between and within cattle and sheep slaughter lines. Samples are contaminated most frequently with Salmonella enterica (28% and 30%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
44
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 74 publications
(48 citation statements)
references
References 30 publications
0
44
0
Order By: Relevance
“…Meat contamination results more often than not during meat slaughtering and processing at the slaughterhouse, causing food poisoning or food-borne diseases and thus precipitating a food safety issue (FAO, 2015;Bakhtiary et al, 2016). Food and meat poisoning are acute foodborne disease caused by contamination and have been common occurrences and a worldwide public health concern (Malangu, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meat contamination results more often than not during meat slaughtering and processing at the slaughterhouse, causing food poisoning or food-borne diseases and thus precipitating a food safety issue (FAO, 2015;Bakhtiary et al, 2016). Food and meat poisoning are acute foodborne disease caused by contamination and have been common occurrences and a worldwide public health concern (Malangu, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…This has re-directed research interest thereby shifting grounds towards food safety and hence has attracted substantial funding and research grants to third world countries for research in food safety, zoonoses and one's health (Grace, 2015;Bardosh et al, 2017). Contamination at the slaughterhouse and contamination of meat occurs because of inadequate hygienic conditions and handling, and may be as a result of the consequence of contaminated air in form of bioaerosol which is loaded with common microbial contaminants like Salmonella, Escherichia, Clostridium (Lues et al, 2007); causing contamination of the carcass/meat, the working surfaces and equipments used in the processing (Bakhtiary et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In this context, microbiological evaluations performed on utensils, environment, and carcasses of cattle, pigs, and sheep in the slaughterhouse of Australia (Bakhtiary et al, 2016), in Mato Grosso (Santos et al, 2017) and Rio de Janeiro (Cabral et al, 2014), Brazil have been reported. In these studies, the occurrence of microorganisms was observed which are indicators of fecal contamination, belonging to the Enterobacteriaceae family, species such as Escherichia coli, and Salmonella enterica in utensils, environment, and carcasses indicating hygiene problems in the slaughter process.…”
Section: Resultsmentioning
confidence: 99%
“…Primer concentration in the reaction volume was 0.5 pM. DGGE gels were prepared as described before by Bakhtiary et al [3], with a linear gradient of 25–65% using a peristaltic pump and run on 175 V for 6 h as described by Remely et al and Hosseini et al [13, 29]. …”
Section: Methodsmentioning
confidence: 99%
“…For all comparisons, P values of ≤0.05 were considered as significant. All data were shown as mean ± SD [3]. …”
Section: Methodsmentioning
confidence: 99%